Fusigen Reduces Intracellular Reactive Oxygen Species and Nitric Oxide Levels - KITIYANANT, VORAWAT (In Vivo, 2019)
Background/Aim: Oxidative stress caused by the production of excessive cellular reactive oxygen species (ROS) and high levels of nitric oxide contribute to several human pathologies. This study aimed to examine the anti-oxidant effects of fusigen, a compound produced from Aureobasidium melanogenum. Materials and Methods: Extracts of A. melanogenum were selected as a source for the isolation of fusigen. The anti-oxidant, nitric oxide suppression, as well as the free radical scavenging activities of fusigen were tested in BEAS-2B human bronchial epithelial cell line (BEAS-2B cells) and human dermal papilla cells (DP cells) using specific fluorescence dyes and flow cytometry analysis. Cell viability was determined by the MTT assay. Results: Fusigen did not exert cytotoxicity in the human normal BEAS-2B and DP cells at concentrations up to 100 μM. Fusigen decreased basal levels of cellular ROS, as well as the levels of ROS induced by hydrogen peroxide and ferrous ion enrichment. ROS decreasing effect was confirmed in DP cells. In addition, fusigen treatment suppressed intracellular NO levels in both BEAS-2B and DP cells. Conclusion: The optimal process of production of purified fusigen from A. melanogenum was determined. Fusigen exhibited a low cytotoxic effect and the potential to suppress ROS and NO. These results demonstrated that fusigen may be used for the treatment or prevention of human diseases.